Analisis Pengaruh Desentralisasi Fiskal terhadap Pertumbuhan Ekonomi kabupaten/kota di Provinsi Jawa Tengah - , M YASSER UMRI; , Prof. Wihana Kirana Jaya, M.Soc.Sc., Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The research aims to give analyze the effect of local revenue, block grants, conditional grants, revenue sharing fund, and capital expenditure on economic growth. The research objects are regency / municipality Central Java Province. The data used in this research taken from 2006-2011 of Province, regency / municipality governments recorded in table of general budget calculation issued by treasury department and table of gross regional domestic product regencies / municipalities in Indonesia issued by central Statistic . The analysis found that local revenue, block grants, conditional grants, revenue sharing fund, and capital expenditure have significant and positive effect on economic growth. It means local governments was able to run fiscal decentralization properly that local government was also able to increase economic growth.